Model Partisipasi Petani dalam Pengembangan Agrowisata di Desa Kerta, Kecamatan Payangan, Kabupaten Gianyar - I WAYAN DEDI SURYAWAN; I WAYAN WINDIA; I MADE SARJANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Farmers Participation Model in Agrowisata Development in Kerta Village,Payangan District, Gianyar Regency. The model of farmer participation in agro-tourism development in Kerta Village,Payangan District, Gianyar Regency is an effort to find out the model of farmerparticipation and farmer participation level in agro-tourism development. The researchlocation is in Kerta Village, Payangan District, Gianyar Regency which is an agro areaof Gianyar Botanical Garden. The method of analysis used is descriptive qualitative.The results showed that the farmers participation model is as follows. (a) Aspects ofmindset; farmers are aware of the potential that exists in Kerta Village that can bedeveloped as agro-tourism. (b) Social aspects; farmers' participation in social aspectssuch as participating in garden arrangement, diversification of commodity diversity,there is also agreement or cooperation between farmer society to sacrifice their land foragro-tourism such as for road and treking. (c) Aspects of artifacts / possessions; peasantcommunity participation in view of the material aspects include the garden andagricultural products, huts / huts for rest, parking lots and public toilets. Farmersparticipation rate is as follows. (a) Manipulation; done by changing the attractiveness ofthe attraction of organic citrus quotes. (b) Dissemination of information; the peasantcommunity conveys information to the general public through word of mouth, socialmedia, billboards installation. (c) Decision-making; demonstrated by their activengrembug to reach joint decisions and participate in village deliberations. (d) Buildingagreements; farmers mutually respect opinion in decision-making to build a deal basedon